Rhizosphere Microbial Community Structure of Transgenic versus Non-Transgenic Maize Varieties (Lafia Journal of Scientific and Industrial Research, 2026)
The soil rhizosphere community is an important indicator of the overall health of the plant, and the resulting yield at harvest. The study determined the rhizosphere microbial community structure of transgenic and non-transgenic maize plants. A farm plot was divided into 4 sections for transgenic maize (SAMMAZ 74T) and non-transgenic variety 8325-8. The maize was infected at the tasseling stage and phenolic content determined after 10 days. The microbial community indices were subsequently determined using metagenomic tools. The physicochemical parameters and microbial population of the soil for maize 8325-8 and SAMMAZ 74T were not significantly differently at P